Efektivitas Servant Leadership Bagi Peningkatan Kinerja Guru Dalam Pengelolaan Pembelajaran di Sekolah - Djami, Denada Isti Novalia (Jurnal Ekonomi, Manajemen, Ilmu Sosial dan Politik, 2025)
This study examines the effectiveness of school principals' servant leadership on improving teacher performance in learning management. Servant leadership, with its focus on service and empowerment, is hypothesized to have a positive impact on teacher performance. A literature study method was used to analyze data from journals, books, and research reports related to the topic. The analysis results indicate that school principals' servant leadership can potentially improve teacher performance by increasing motivation, competence, positive work climate, learning innovation, and communication. Further research is needed to develop a contextual servant leadership model and examine the factors influencing its effectiveness at various educational levels.